Knowledge about Type Diabetes Mellitus : A Descriptive Study in Mujahidin High School Pontianak - Oktaviani, Cindy; Fradianto, Ikbal; Rahmah, Gabby Novikadarti (Universitas Airlangga, 2025)
Introduction: Technological developments and exposure to social media content that promote unhealthy foods have contributed to an increase in cases of type 2 diabetes mellitus,especially among children and adolescents. Although no specific data is currently available regarding the incidence of type 2 diabetes mellitus in adolescents in Indonesia, there has been a significant rise in the prevalence of overweight adolescents. This study aims to describe the level of knowledge about type 2 diabetes mellitus among adolescents at SMA Mujahidin Pontianak. Methods: This research employs a quantitative approach with descriptive research methods. The sampling technique used is stratified random sampling, involving a total of 245 students from grades X and XI at SMA Mujahidin Pontianak. The instrument used in this research was the DKQ-24 questionnaire, which was administered to the respondents. Data were analyzed using univariate analysis. Results: The findings indicated that 76.7% (188 respondents) had a moderate level of knowledge about type 2 diabetes mellitus, 17.6% (46 respondents) had a low level of knowledge, and 15.7% (11 respondents) demonstrated a high level of knowledge. Conclusion: The majority of students at SMA Mujahidin Pontianak possess a moderate level of knowledge about type 2 diabetes mellitus. The study recommends that schools collaborate with healthcare professionals or health organizations to create informative materials,such as posters about type 2 diabetes mellitus, and to strengthen the school health program (UKS) to enhance students' knowledge and awareness.